Chemical Thermodynamics, 1/e : Classical, Statistical and Irreversible. - Rajaram, J. (2012)
Aimed at providing undergraduate and postgraduate students with an understanding of this subject, the book brings out the thermodynamic interrelationships by explaining its essential elements. It begins with the fundamentals and progresses to advanced concepts to enable students to appreciate the application of thermodynamics in different areas of chemistry. Chemical Thermodynamics is course textbook is written in a simple and lucid language, the discussion and explanations being interspersed with appropriate worked-out examples. Every chapter is accompanied by adequate end-of-chapter exercises.
12.b.3. Determination of the Activities and Activity Coefficients of Strong Electrolytes -- 12.c. Ionic Strength -- 12.d.1. Activity Coefficients from Solubility Measurements -- 12.d.2. Results of Activity Coefficient Measurements -- 12.d.3. Activity Coefficients from Debye-Huckel Theory -- 12.e.1. Applications of the Debye-Huckel Limiting Law -- 12.e.2. Verification of the Limiting Law -- 12.f. Thermodynamics of Ions in Solution -- Questions -- Appendix A : Thermodynamic Properties of Systems Under the Influence of Various Fields -- Appendix B : Non-equilibrium Thermodynamics or Thermodynamics of Irreversible Processes -- Appendix C : A Molecular Approach to Internal Energy and Enthalpy -- Appendix D : A Few Applications of Quantum Statistics -- Appendix E : Tables : List of tables A to H -- Bibliography -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books